T 2 Clusters Are More Sensitive Than Mean T 2 Change to Detect Early and Longitudinal Changes in Anterior Cruciate Ligament Reconstructed and Healthy Knees - Pai S, Anoosha; Gatti, Anthony A.; Black, Marianne S.; Young, Katherine A.; Desai, Arjun D.; Barbieri, Marco; Asay, Jessica L.; Sherman, Seth L.; Gold, Garry E.; Kogan, Feliks; Hargreaves, Brian A.; Chaudhari, Akshay S. (Journal of magnetic resonance imaging, 2025)
Post-traumatic osteoarthritis (PTOA) often follows anterior cruciate ligament reconstruction (ACLR), leading to early cartilage degradation. Change in mean T fails to capture subject-specific spatial-temporal variations, highlighting the need for robust quantitative methods for early PTOA detection and monitoring. Develop and apply 3D T cluster analysis to ACLR and healthy knees over 2.5 years. Longitudinal case-control study. ACLR and contralateral knees of 15 subjects (9 male/6 female, 37.7 ± 10 years) and right knee of 15 matched controls (9 male/6 female, 37.1 ± 12 years) were scanned at 3 weeks, 3, 9, 18, and 30 months post-ACLR. 3 T Quantitative double echo steady state sequence. "T cluster analysis" was developed, incorporating registration and thresholding methods to identify and quantify elevated T regions (T clusters, T C) in femoral cartilage. Percentage of cartilage covered by T clusters (T C ), mean cluster size (T C ), the number of clusters (T C ), and ΔT Mean (change in mean femoral cartilage T relative to visit 1) were computed for all knees. A linear mixed model assessed knee, time, and knee-time interaction effects on each outcome metric (P < 0.05), with effect sizes (η ) describing the sensitivity of these effects to longitudinal changes. T C (η = 0.22), T C , (η = 0.14), and T C (η = 0.51) showed significant and systematic difference between knees (ACLR > contralateral > control). T C (η = 0.24), T C (η = 0.17), and T C (η = 0.11) showed significant longitudinal change across all knees. Specifically, ACLR knees exhibited a significant increase in T C (η = 0.21), T C (η = 0.13), and a decrease in T C (η = 0.07) with time. ΔT Mean showed significant difference between knees (η = 0.15), increase with time (η = 0.04), with no significant knee-time interaction (η = 0.00, P = 0.772 [contralateral], P = 0.482 [control]). T C metrics are more sensitive than ΔT Mean for longitudinal monitoring of femoral cartilage post ACLR. Our findings suggest potential merging of T clusters overtime, forming larger areas of cartilage degradation in ACLR knees. 1 TECHNICAL EFFICACY: Stage 2.